Emotion regulation in childhood: Delimitation and definition - Rocha, Ana Maria (2018)
This article makes a conceptual and theoretical review of emotion regulation, as well as empirical studies associated with correlates and psychosocial adjustment indicators. Within Developmental Psychology, this article aims to contribute to the definition and delimitation of emotion regulation in childhood. To do this, we begin by making a historical overview of its study; then we seek to delimitate the term over others that are contiguous (e.g., coping and emotional intelligence), to then provide a definition focusing in several issues that are relevant to the topic (e.g., emotion regulation and emotional regulation, self-regulation and external regulation of emotions).